KEHIDUPAN SOSIAL PEDAGANG ASONGAN DALAM KARYA SENI LUKIS REALIS KONTEMPORER - RUDI RAHMAT, Drs. Erfahmi, M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
The aim of the thesis is to visualize the social life of hawkers into contemporary realist painting. The hawkers have also varied from child, teenagers, adults, men and women. There are five methods used in creating this, thesis, they are: preparation, elaboration stage, the stage of synthesis, and the realization phase began sketching concepts, moving sketch, preparation of tools and materials, working and finishing processes. The last stage is the completion of up to exhibit. Ten appointed work is to visualize the social life of hawkers in the works of contemporary realist painting as a great struggle carried hawkers to be able to continue to live under economic pressure.Kata kunci: Kehidupan sosial pedagang asongan, realis kontemporer